Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1038/nnano.2011.38
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional bicontinuous ultrafast-charge and -discharge bulk battery electrodes

Abstract: Rapid charge and discharge rates have become an important feature of electrical energy storage devices, but cause dramatic reductions in the energy that can be stored or delivered by most rechargeable batteries (their energy capacity). Supercapacitors do not suffer from this problem, but are restricted to much lower stored energy per mass (energy density) than batteries. A storage technology that combines the rate performance of supercapacitors with the energy density of batteries would significantly advance p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
706
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,027 publications
(717 citation statements)
references
References 38 publications
2
706
0
3
Order By: Relevance
“…These materials can also be filled with electrolytes that are liquid or polymer based, forming interpenetrating networks. Recent demonstrations have shown that ultrafast-charging batteries can be fashioned by controlling porosity in active materials [517][518][519][520][521]. The downside is the severe reduction in specific energy due to the porosity, but the technology may prove useful for large surface area applications.…”
Section: Discussionmentioning
confidence: 99%
“…These materials can also be filled with electrolytes that are liquid or polymer based, forming interpenetrating networks. Recent demonstrations have shown that ultrafast-charging batteries can be fashioned by controlling porosity in active materials [517][518][519][520][521]. The downside is the severe reduction in specific energy due to the porosity, but the technology may prove useful for large surface area applications.…”
Section: Discussionmentioning
confidence: 99%
“…Because the nanoparticles are fully embedded in the matrix, they do not dislodge from the structure, and the efficiency is stable even after hundreds of cycles ( Figure 28B). 62 Alternatively, active electrode materials can easily be grown on conducting supports to produce a layered structure, 26,415,416,425,465 as shown in Figure 29. With hierarchical structures, the charge can quickly travel from the active site to the conducting matrix, where it can be collected before recombination.…”
Section: Factors Influencing Electrode Applicationsmentioning
confidence: 99%
“…Recently, Zhang et al have shown that inverse opal structures consisting of conductive metal backbones and electrolytically active phases can offer rapid charge and discharge rates while maintaining a fairly modest energy density. 13,14 However, the particular pore conguration of an inverse opal (spherical pockets connected by small interstitial windows) does not lend itself to the level of morphological control needed to independently tune the electrode's capacity and power density while also conserving the required co-continuity to avoid current constriction in the charge carrier transport pathways. The fabrication technique also limits the height of the electrode to $15 mm, restricting the total amount of stored energy in these systems.…”
Section: Introductionmentioning
confidence: 99%